Circadian and Seasonal Patterns of Body Temperature in Arctic Migratory and Temperate Non-migratory Geese - Eichhorn, Götz; Boom, Michiel P.; van der Jeugd, Henk P.; Mulder, Amerins; Wikelski, Martin; Maloney, Shane K.; Goh, Grace H. (Frontiers in Ecology and Evolution, 2021)
Arctic migration presents unique challenges to circadian physiology. In addition to the metabolic cost of maintaining a relatively high body temperature (Tb) above ambient temperature, migratory birds are also exposed to rapidly changing light conditions as they transition between light-dark cycles and a 24-hour polar day. A previous study suggested that Arctic-migratory barnacle geese (Branta leucopsis) may utilise adaptive heterothermy (i.e., a controlled decrease in core Tb) during and around the autumn migratory period in order to minimise the metabolic cost of migration, but the impact of seasonally changing daylight conditions on other parameters of the circadian profile of Tb in these geese remained obscure. Here, we provide a detailed comparative analysis on the circadian rhythm of Tb and its seasonal development in free-living barnacle geese from three study populations that differ in their migratory behaviour and in the environments they occupy. We recorded abdominal Tb in non-migratory geese from a temperate breeding colony in the Netherlands and in migratory geese from a colony in the Russian low Arctic, and analysed these data together with previously published Tb data on geese from a migratory colony in the high Arctic of Svalbard. We found that the circadian Tb profile in the barnacle goose was well aligned with the daily and seasonally changing daylight conditions. In the migratory populations, a fast re-entrainment of the rhythm and its phase was observed when zeitgeber conditions changed during migratory movements. The circadian rhythmicity of Tb was lost once the geese encountered permanent daylight at their northern staging and breeding sites. Circadian Tb rhythmicity was re-established when the period of permanent daylight ended, at rates corresponding to rates of seasonal changes in daylength in the high and low Arctic. Although our data corroborated findings of a decrease in daily mean Tb before autumn migration in both migratory populations in this study, the pre-migratory decrease in Tb was less drastic than previously reported. Moreover, in contrast to previous study, the decrease in Tb stopped at the onset of migration. Overall, our data reveal no evidence that heterothermy in the barnacle goose is functionally linked to migration.